An analysis of tools for online anonymity. Issue 4 (2nd November 2015) - Winkler, Stephanie; Zeadally, Sherali
Abstract : Purpose: – The purpose of this paper is to examine the possible explanations for the slow adoption and development of online anonymity technology. The ability to remain anonymous while engaging in different activities, online is increasingly sought after by consumers with privacy concerns. Currently, the only way to maintain online anonymity is through the use of technology. This paper reviews and analyzes the tools currently available to consumers to maintain online anonymity. There are only four tools available to consumers to ensure online anonymity: anonymous remailers, rewebbers, The Onion Router (Tor) and the Invisible Internet Project (I2P). These tools provide the protection needed for an Internet user to remain anonymous but suffer from a lack of usability and adoption. Design/methodology/approach: – The authors have selected a few specific online anonymity technologies based on the following criteria: the technology satisfies our full anonymity definition, the technology is currently available for public use and the technology has been academically researched. Findings: – Few anonymity technologies are available for public use that offer the ability for full online anonymity, and these technologies are difficult for the average computer user to operate. Further research is still needed to help determine what the average user wants to see in an anonymity technology as well as ways to help users integrate the technology into their commodity software (such as Web browsers). Future online anonymity technologies should enable the user to decide when, how and with whom their information is shared if it is shared at all with ease and simplicity. Originality/value: – The authors identify, explain and analyze publicly available online anonymity technologies in terms of their usability. The authors identified ways as to how online anonymity technology can be improved to increase public adoption. The authors make pertinent recommendations on how the design and development of online anonymity technology can be improved in the future.